2014
DOI: 10.1007/s10943-014-9978-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep Quality and Spiritual Well-Being/Religious Activities in Muslim Women with Breast Cancer

Abstract: For determining relationship between quality of sleep and spiritual well-being/religious activities in Muslim women with breast cancer (WBC), we conducted a cross-sectional study on 80 WBC who presented at all chemotherapy clinics in Qom, Iran, in 2012. We used Pittsburgh Sleep Quality Index (PSQI), spiritual well-being scale (SWBS), and religious activities (RA) questionnaire. Global PSQI score and its seven components score were not significantly correlated with total score of SWBS and its two subscales. Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
3
13
0
1
Order By: Relevance
“…Other quantitative studies investigated the relationship between spirituality (or a related spiritual concept such as spiritual wellbeing or spiritual health) and quality of life (Khoramirad et al 2015), and coping strategies (Amjad and Bokharey 2015). Three studies focused on instrument design and validation (Cruz et al 2016;Jafari et al 2013;Lazenby et al 2013).…”
Section: Quantitative Researchmentioning
confidence: 99%
“…Other quantitative studies investigated the relationship between spirituality (or a related spiritual concept such as spiritual wellbeing or spiritual health) and quality of life (Khoramirad et al 2015), and coping strategies (Amjad and Bokharey 2015). Three studies focused on instrument design and validation (Cruz et al 2016;Jafari et al 2013;Lazenby et al 2013).…”
Section: Quantitative Researchmentioning
confidence: 99%
“…We should note that although our study centers on population‐based research, a number of clinical studies have also made important contributions to the study of religion and sleep (e.g., Khoramirad et al. ; Kopp et al. ; Vidal and Shocat ).…”
mentioning
confidence: 99%
“…Although prior qualitative work suggests the value of spirituality to support sleep among a sample of women with advanced breast cancer [9], little research has been done to assess the relationship between spirituality and sleep disturbance among cancer patients. One prior study examined spirituality and sleep quality among Muslim women with breast cancer and found that some aspects of spirituality may predict better sleep quality, although the overall correlation between spiritual well-being and quality of sleep was non-signi cant [40]. These ndings underscore the potential importance of addressing spirituality as part of holistic symptom management, yet additional research is needed to examine the role of spirituality (and its sub-components) in the experience of cancer-related symptoms among larger and more diverse samples.…”
Section: Discussionmentioning
confidence: 99%